REVIEW: CORN COB POTENTIAL FOR APPLICATIONS IN COMMERCIAL PRODUCTS - Sebastianus Dani Ganesha; Salsabila Maris Syahputri; Samuel Yedija Liem; Joko Prasetyo; Harum Azizah Darojati (Jurnal Forum Nuklir, 2021)
Post-harvest activities of agricultural products often generate wastes. One of the agricultural wastes that increase every year is corn cobs, which have a high cellulose content and can potentially be used as raw materials for making natural fibers. Therefore, this study aims to examine the several potential commercial products from corn cobs. The method used is a literature study by tracing the sources of previous writings. Furthermore, how to process corn cobs waste for the manufacture of natural fibers and commercial products will be discussed. From the previously traced sources in the utilization of corn cobs waste, 4 products were obtained. The results are nano hydrogels based on gamma radiation, activated carbon with a carbonation process, bioethanol using the SSF process, and the use of corn cob cellulose as good-quality brake lining.